2019
DOI: 10.1016/j.molcel.2019.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Nucleo-cytoplasmic Partitioning of ARF Proteins Controls Auxin Responses in Arabidopsis thaliana

Abstract: Highlights d Condensation of transcription factors to attenuate hormone response d Mechanism for nucleo-cytoplasmic partitioning of transcription factors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
221
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 211 publications
(243 citation statements)
references
References 76 publications
(113 reference statements)
20
221
2
Order By: Relevance
“…). Interestingly, recent work has found that some activating ARF proteins form biomolecular condensates in a tissue specific manner within the plant …”
Section: Arf Condensate Formation To Regulate Auxin Responsementioning
confidence: 99%
See 4 more Smart Citations
“…). Interestingly, recent work has found that some activating ARF proteins form biomolecular condensates in a tissue specific manner within the plant …”
Section: Arf Condensate Formation To Regulate Auxin Responsementioning
confidence: 99%
“…). Indeed, both the PB1 domain and intrinsically‐disordered MR contribute to ARF condensate formation in planta …”
Section: Arf Condensate Formation To Regulate Auxin Responsementioning
confidence: 99%
See 3 more Smart Citations